Bioabsorbable bone fixation plates for X‐ray imaging diagnosis by a radiopaque layer of barium sulfate and poly(lactic‐co‐glycolic acid). Issue 3 (26th June 2014) - Choi, Sung Yoon; Hur, Woojune; Kim, Byeung Kyu; Shasteen, Catherine; Kim, Myung Hun; Choi, La Mee; Lee, Seung Ho; Park, Chun Gwon; Park, Min; Min, Hye Sook; Kim, Sukwha; Choi, Tae Hyun; et al.
Abstract: Bone fixation systems made of biodegradable polymers are radiolucent, making post‐operative diagnosis with X‐ray imaging a challenge. In this study, to allow X‐ray visibility, we separately prepared a radiopaque layer and attached it to a bioabsorbable bone plate approved for clinical use (Inion, Finland). We employed barium sulfate as a radiopaque material due to the high X‐ray attenuation coefficient of barium (2.196 cm 2 /g). The radiopaque layer was composed of a fine powder of barium sulfate bound to a biodegradable material, poly(lactic‐ co ‐glycolic acid) (PLGA), to allow layer degradation similar to the original Inion bone plate. In this study, we varied the mass ratio of barium sulfate and PLGA in the layer between 3:1 w/w and 10:1 w/w to modulate the degree and longevity of X‐ray visibility. All radiopaque plates herein were visible via X‐ray, both in vitro and in vivo, for up to 40 days. For all layer types, the radio‐opacity decreased with time due to the swelling and degradation of PLGA, and the change in the layer shape was more apparent for layers with a higher PLGA content. The radiopaque plates released, at most, 0.5 mg of barium sulfate every 2 days in a simulated in vitro environment, which did not appear to affect the cytotoxicity. The radiopaque plates also exhibited good biocompatibility, similar to that of the Inion plate. Therefore, we concluded that the barium sulfate‐based, biodegradable plate prepared in this work has the potential to be used as a fixation device with both X‐ray visibility and biocompatibility. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B:596–607, 2015.